Procalcitonin levels in sepsis and its association with clinical outcome in southern India. (October 2017) - Rebello, Alex; Thabah, Molly Mary; Dutta, Tarun Kumar; Bobby, Zachariah; Harish, BN; Mehalingam, Vadivelan
Procalcitonin has been found to be a good marker for the diagnosis of sepsis. However, data on procalcitonin levels to predict the clinical outcome in patients with sepsis are limited. The aim of our study was to estimate serum procalcitonin levels in patients with sepsis and to identify its relationship with the clinical outcome. This was a prospective observational study conducted on 112 patients with sepsis admitted to the medical wards and medical intensive care unit of a tertiary care teaching hospital. Serum procalcitonin was measured at baseline before antibiotic administration and on day 5. The clinical outcome studied was death or survival on day 28. Baseline mean serum procalcitonin was highest in patients with septic shock and lowest in patients having sepsis without organ dysfunction. Mean values of procalcitonin at baseline and on day 5 were significantly higher in non-survivors when compared with survivors. There was a significant difference in the change in procalcitonin levels from baseline to day 5 between survivors and non-survivors, with survivors having declining values on day 5 while non-survivors had increasing values from baseline. The baseline APACHE II and SOFA scores also showed a significant correlation with the baseline procalcitonin level. Declining values of procalcitonin therefore indicate a favourable clinical outcome in patients with sepsis.